User experience in using surface computing for collaborative decision making - Zaphiris, Panayiotis; Ioannou, Andri; Loizides, Fernando; Vasiliou, Christina (My University, 2013)
Purpose – This paper aims to report work regarding the design, development and evaluation of a surface computing application to support collaborative decision making. The domain-independent application, the so-called Ideas Mapping, builds on the principle of affinity diagramming to allow participants to analyze a problem and brainstorm around possible solutions, while they actively construct a consensus artifact – a taxonomy of their ideas. Design/methodology/approach – Ideas Mapping was designed using a user-centred approach. During idea generation, Ideas Mapping replicates physical post-it notes on a multi-touch tabletop. Additional functionality supports student collaboration and interaction around the organization of ideas into thematic categories associated with the problem at hand. The tool was evaluated in two studies using quantitative and qualitative data. Findings – The paper reports on the functionality and user experience while interacting with the application. The paper also reports initial findings regarding the affordances of surface computing for collaborative decision making. Originality/value – The studies reported give insides regarding the affordances of multi-touch tabletops to support collaborative decision making. Information regarding the user experience in using such applications is reported.
Keywords: Communication technologies; Multimedia